The development and validation of maternal spiritual characteristics scale. - Hassan, Siti Aishah; Mohd Noah, Sidek; Abdullah, Abdullah Seif; Ishak, Noriah (Common Ground Publishing Pty Ltd, 2008)
The purpose of this study is to develop and validate a family counseling instrument that measures maternal spiritual characteristics. Particularly, the instrument aims to measure three domains of spirituality namely, Maternal Piety, Mercy and Accountability. These characteristics are considered as the characteristics for functional Muslim mothers. The study is designed into three phases. The first phase is a pilot study of a focus group from an Islamic Integrated Primary School (IIPS). In this phase, Cronbach’s alpha is employed to assess the reliability index. Accordingly, Principle Component Analysis is employed to explore the underlying dimensions of Maternal Piety, Mercy and Accountability. The second phase is an ex-post facto study that involved 12 IIPS in the Klang Valley of Malaysia. Confirmatory factor analysis (CFA) is utilized to examine the construct validity of the instrument. Structural Equation Modeling (SEM) is used to investigate the relationship between maternal spiritual characteristics and mother-child attachment as supporting evidence for the criterion-related validity. The third phase was a cross-sectional study that involved 1000 students (age 13-17) from various secondary schools (inclusive of religious and non religious schools) of 4 states in Malaysia. In this phase, multistage cluster sampling technique is employed to select 200 students from each age group of Form 1,2,3,4 and 5. The results provide evidence that the instrument has sound psychometrics properties. This instrument has succeeded the standard Cronbach’s alpha > .70 for internal consistency and proportion variance explained > 50 % for the dimensions of Maternal Piety , Mercy and Accountability . The goodness-of -fit measures GFI, AGFI, IFI, TLI, and CFI > .90 and RMSEA < .08 are evidences for construct validity. Moreover, the criterion-related validity is supported with the findings of significant positive relationship between maternal spiritual characteristics and mother-child attachment. In short, Maternal Spiritual Characteristics Scales (MSCS) is a reliable and valid instrument. Hence, it may be used for the assessment in family counseling and other related studies.